(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
When it comes to a country’s economic development and international status, internationalcommerce is crucial. As one of the world’s fastest-growing economies, India’s role in global commercehas undergone dramatic change in recent decades. This research aims to examine India’s internationaltrade practices by determining the driving forces behind India’s exports and imports, cataloging thecountry’s most important trading partners and commodities, and assessing the results for India’seconomic growth. The research is all-encompassing it uses both qualitative and quantitative approaches.Primary data sources consist of government reports, official trade figures, and the opinions ofpolicymakers and trade specialists. Secondary sources include scholarly journals, books, and reportsfrom recognized international institutions.